A physical map for the Amborella trichopoda genome sheds light on the evolution of angiosperm genome structure - Zuccolo, Andrea (BioMed Central, 2011)
BACKGROUND: Recent phylogenetic analyses have identified Amborella trichopoda, an understory tree species endemic to the forests of New Caledonia, as sister to a clade including all other known flowering plant species. The Amborella genome is a unique reference for understanding the evolution of angiosperm genomes because it can serve as an outgroup to root comparative analyses. A physical map, BAC end sequences and sample shotgun sequences provide a first view of the 870 Mbp Amborella genome. RESULTS: Analysis of Amborella BAC ends sequenced from each contig suggests that the density of long terminal repeat retrotransposons is negatively correlated with that of protein coding genes. Syntenic, presumably ancestral, gene blocks were identified in comparisons of the Amborella BAC contigs and the sequenced Arabidopsis thaliana, Populus trichocarpa, Vitis vinifera and Oryza sativa genomes. Parsimony mapping of the loss of synteny corroborates previous analyses suggesting that the rate of structural change has been more rapid on lineages leading to Arabidopsis and Oryza compared with lineages leading to Populus and Vitis. The gamma paleohexiploidy event identified in the Arabidopsis, Populus and Vitis genomes is shown to have occurred after the divergence of all other known angiosperms from the lineage leading to Amborella. CONCLUSIONS: When placed in the context of a physical map, BAC end sequences representing just 5.4% of the Amborella genome have facilitated reconstruction of gene blocks that existed in the last common ancestor of all flowering plants. The Amborella genome is an invaluable reference for inferences concerning the ancestral angiosperm and subsequent genome evolution.